PENTINGNYA PENDIDIKAN ANTIKORUPSI SEBAGAI MATA KULIAH DI KAMPUS - Ni Wayan Intan Widyantari (Ganesha Civic Education Journal, 2022)
The eradicating corruption to its roots can't only be done through taking action and punishing corruptors as fairly as possible. This is because corruption exists as a hereditary inheritance which causes it to be born as a bad culture of the nation. Bad culture can be trimmed through education. Education was born as a tool to form human hard skills or soft skills. So to cut this culture, anti-corruption education is needed to show techniques to students so that students are able to clearly understand the problems of corruption that occur. This article explains anti-corruption education and to understand how this education is given to students as an effort to eradicate corruption. Efforts to provide insight can be through various ways, namely socialization, campaigns, seminars, and lectures. Anti-corruption education aims to transfer knowledge about Pancasila values that are not pro-corruptive culture. The goal of sustainability of this anti-corruption education is to foster a community spirit that is far from corrupt actions so that it encourages national development which starts here with education for students as the successors of the nearest nation who are able to continue the baton of the next nation's leadership which is far from a culture of corruption.